PERANAN SISTEM INFORMASI AKUNTANSI (MICROSOFT EXEL) PADA KINERJA KEUANGAN TOKO KUE ACHI’S CAKE TERHADAP MINAT BELI KONSUMEN - Ari Setyo Wati; Hwihanus Hwihanus (Trending: Jurnal Manajemen dan Ekonomi, 2023)
Achi's Cake is one of the cake shop businesses in the city of Jombang. In cake sales, orders and cake sales are entered manually into the general ledger, just as in the sales process, transactions are calculated and written manually into sales invoices. In addition, the price of the product depends on the price of raw materials. From these problems, the authors use Microsoft Exel accounting software to help the bakery business in the form of an accounting information system. This data collection technique uses interview techniques, and data analysis uses SPSS accounting software: Interviews, namely a meeting of two people to exchange information and ideas through question and answer which is used to obtain data information about the Achi's Cake business. Then the second uses SPSS data analysis to determine consumer interest before and after Achi's Cake uses Microsoft Exel in recording its financial reports. In this study the authors processed data using SPSS accounting software to analyze consumer interest before using Microsoft Exel (X1), consumer interest after using Microsoft Exel (X2) and consumers (Y). A random sample of 10 consumers was taken, who had already bought Achi's Cake products so they already knew the performance of Achi's Cake's business. From the results of user testing it can be concluded that Achi's Cake's accounting information system uses Microsoft Exel accounting software with SPSS testing which is useful for Achi's Cake's performance to determine the effect before and after using Microsoft Exel's accounting information system software on consumer buying interest.